2016
DOI: 10.1111/aos.13175
|View full text |Cite
|
Sign up to set email alerts
|

Combination of 5% phenylephrine and 0.5% tropicamide eyedrops for pupil dilation in neonates is twice as effective as 0.5% tropicamide eyedrops alone

Abstract: The dilated pupil surface area for the combination of 5% phenylephrine and 0.5% tropicamide was almost twice that for 0.5% tropicamide eyedrops alone and provided significantly superior quality of the eye fundus examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…14 15 ► In addition, the ophthalmologist scores on the ease of the ROPEE on the scale of very easy, easy, no difference, difficult or very difficult. These outcomes measures are similar to those reported by Lux et al 18 ► Photos of both eyes were obtained using a camera, with the eye illuminated. ► Photos were imported into the GIMP V.2.8.20 image manipulation program, where the measure tool was used to measure the pupil diameter and compare with the metric graduated colour tool.…”
Section: Methodssupporting
confidence: 81%
“…14 15 ► In addition, the ophthalmologist scores on the ease of the ROPEE on the scale of very easy, easy, no difference, difficult or very difficult. These outcomes measures are similar to those reported by Lux et al 18 ► Photos of both eyes were obtained using a camera, with the eye illuminated. ► Photos were imported into the GIMP V.2.8.20 image manipulation program, where the measure tool was used to measure the pupil diameter and compare with the metric graduated colour tool.…”
Section: Methodssupporting
confidence: 81%
“…Ogut (1996)26 results were not able to be included because p values were not presented. Luo (2014)21 commented that no infants had bradycardia, and Lux’s (2016)27 study design intended to collect data on pulse rate and blood pressure but did not provide results for this.…”
Section: Resultsmentioning
confidence: 99%
“…Lux’s (2016)27 study design intended to collect data on oxygen saturation and respiratory frequency but did not provide results for this 27…”
Section: Resultsmentioning
confidence: 99%
“…In the USA, this agent is often paired with the sympathomimetic drop phenylephrine hydrochloride at 2.5% concentration. When 0.5% tropicamide is paired with 5% epinephrine eyedrops, a study found that premature infants undergoing screening for retinopathy of prematurity achieved twice the dilated pupil surface area with the combination of drugs compared to 0.5% tropicamide alone [ 24 ]. Like other agents in its class, this agent can blur vision and in rare cases cause an attack of acute angle-closure glaucoma so angle-closure risk must be assessed prior to instillation.…”
Section: Cycloplegic/pain Control Agentsmentioning
confidence: 99%